2021
DOI: 10.3389/fmech.2021.661422
|View full text |Cite
|
Sign up to set email alerts
|

Adhesive Droplets of Glowworm Snares (Keroplatidae: Arachnocampa spp.) Are a Complex Mix of Organic Compounds

Abstract: Adhesive snares built from silks are fascinating adaptations that have rarely evolved outside spiders. Glowworms (Arachnocampa spp.) are an iconic part of the fauna of Australia and New Zealand that combine the construction of a sticky snare with a bioluminescent lure. Recently, the structure and biomechanical properties of glowworm silk have been studied in detail, but the chemical composition of its adhesive coating, and how it varies between species of Arachnocampa remained unclear, limiting an understandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Given the comparatively low diversity of compounds residing in the glues of the species examined herein, it seems that adhesion is attained by a similar biochemical means across species. By examining the chemistries of a wider range of spider glues, as well as the glues of other animals that produce glues with similar functionalities, e.g., comb jellies, mussels, velvet worms, and Arachnocampa glow worms (von Byern et al, 2017;Blamires, 2019;Wolff et al, 2021), common features underlying the functionality of all animal PSAs could be revealed, demonstrating a promising bioprospecting approach for the design of novel, sustainable, adhesives with extended functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the comparatively low diversity of compounds residing in the glues of the species examined herein, it seems that adhesion is attained by a similar biochemical means across species. By examining the chemistries of a wider range of spider glues, as well as the glues of other animals that produce glues with similar functionalities, e.g., comb jellies, mussels, velvet worms, and Arachnocampa glow worms (von Byern et al, 2017;Blamires, 2019;Wolff et al, 2021), common features underlying the functionality of all animal PSAs could be revealed, demonstrating a promising bioprospecting approach for the design of novel, sustainable, adhesives with extended functions.…”
Section: Discussionmentioning
confidence: 99%
“…As animal adhesives are usually a diverse and variable mix of components (Wolff et al, 2021), identifying the core functional units leading to the impressive performance represents a major milestone toward a successful biomimetic implementation. One way to achieve this is through the comparative study of analogous systems (Wolff et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Rheological properties of the P. shermani glue indicate a high water loss after secretion with a total weight loss of around 70% (von Byern et al, 2017a). While also in other species a water content of 85-90% (in the frog Notaden) or even up to 98% in the New Zealand glowworm larvae Arachnocampa luminosa could be measured (von Byern et al, 2017a;Wolff et al, 2021) a clear indication for a hydrodynamic performance after secretion is not stated. Up to know, no information is given for H. dunni, however a weight loss due to glue curing could likewise be observed.…”
Section: Tribological Properties Of Salamander Gluesmentioning
confidence: 94%
“…Both larval survival and the adhesiveness of the snares require the high humidity found in caves and rain forests (von Byern et al, 2019). The ability of the snares to function effectively at high humidity, was recently investigated by Wolff et al (2021), who found that polar substances and hygroscopic compounds in the glue droplets, especially urea and a range of amino acids, were responsible for their function, although interestingly, variation was found both between species and between forest and cave populations (Wolff et al, 2021). Thus, glowworm glue droplets may serve as inspiration for developing moisture resistant and moisture activated adhesives that are required to function in environments with a constant high humidity, which would, for example, be useful as tissue adhesives in surgery (Wolff et al, 2021).…”
Section: Cave Biomimeticsmentioning
confidence: 99%